Use of Escherichia coli operon-fusion strains for the study of glycerol 3-phosphate transport activity. - Miki, K (1980)
Strains of Escherichia coli K-12 deleted in the native lac operon and bearing both a wild-type glpT operon encoding for sn-glycerol 3-phosphate (G3P) transport and a hybrid operon in which glpT operator and promoter regions are fused to the lacZ gene were constructed. In strains with such a hybrid operon, beta-galactosidase and beta-galactoside permease become inducible by G3P. In these mutants the function and maturation of the glpT-coded proteins should be distinguishable from the level of gene expression, since the beta-galactosidase activity can serve as an index of the latter. With the aid of such mutants, it was shown that: (i) the expressions of the two neighboring operons, glpT and glpA (encoding anaerobic G3P dehydrogenase), are not coordinate; (ii) upon induction, the appearance of the cytoplasmic beta-galactosidase activity preceded that of methyl-beta-D-thiogalactoside transport activity (requiring only a cytoplasmic membrane protein) by about 4 min and that of G3P transport activity (requiring both a cytoplasmic membrane protein and a periplasmic protein) by about 9 min; and (iii) when cells grown at several temperatures from 24 to 42 degrees C were measured for G3P transport activity at 30 degrees C, the activity increased with the growth temperature, indicating that, within the range studied, the rate of transport increases with the fluidity of membrane phospholipids.